OPTIMALISASI JUMLAH BATU BATA YANG PECAH MENGGUNAKAN DESAIN EKSPERIMEN TAGUCHI (Studi Kasus: Usaha Batu Bata Bapak Kholil Ds. Bulak Karangawen) - Cakra Kurniawan; Hasbi Yasin; Sugito Sugito (Jurnal Gaussian, 2014)
Brick is a substansial element in building construction. The strength of building may depend on bricks, a solid construction uses the best quality brick’s, which is not crumbling and broken into two parts. There are two popular types of bricks in Semarang, Penggaron bricks and Welahan bricks, Penggaron bricks is the most desirable type in market, but the quality of Penggaron bricks is worse than Welahan bricks, because the Penggaron bricks broken pieces are much more than Welahan’s. So that Penggaron bricks were taken to do research in purpose of optimizing the number of brick’s broken pieces that occurred during the production process. The method being used was the "Taguchi Design of Experiments" using Smaller is Better as quality character. The outcome of pre-experimental study was 3 factors and 2 levels so that L4 Orthogonal Array was used. After analyzing and conducting confirmation experiment, the result was obtained as follow, at the initial conditions, there are 4.6% of broken bricks, the broken bricks became 1.8%, after the experiment. The 1.8% of broken bricks were still within the range of the predicted value 1% to 2%.